EFL Learners’ Attitude toward Educational Technology-: A View from the Appraisal Theory - Marsakawati, Ni Putu Era; Ragawanti, Debora Tri (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
This study cultivated students’ attitudes toward educational technology through the appraisal theory. To achieve this aim, data were collected from the written responses of the open-ended questionnaire written by 40 students majoring in English Language Education Department in one of state university in Bali taking Strategy and Learning Design Course. The collected data were analyzed qualitatively by following Martin White' s (2005) framework of appraisal theory. The findings revealed that the EFL students had a positive attitude toward the educational technology used in the classroom. It is evident from their positive reaction-appreciation and valuation-appreciation of the education technology. It is also apparent from their capacity-judgment about their capability and learning performance and their positive emotional reactions to educational technology. Another point highlighted is the connection between their attitude and principles of technology and pedagogy. The results suggest lecturers integrate educational technology with the educational principles for effective teaching.